Creating Shared Value and Determinants of Sustainable Business Performance: Insights from a Literature Review - Musfar, Tengku Firli; ‎ , Zulkarnain; Alwie, Alvi Furwanti; Wijayanto, Gatot (KnE Social Sciences, 2024)
This article presents a comprehensive exploration, rooted in a literature review, aiming to elucidate the nexus between Creating Shared Value (CSV) and the determinants of sustainable business performance. In the contemporary business landscape, environmental sustainability has evolved beyond a moral responsibility and become a strategic business opportunity for modern companies. The methodology employed in this study involves conducting an extensive literature review. Through the analysis of existing literature, the research synthesizes insights into the relationship between CSV and sustainable business performance. The focus is on theoretical exploration, elucidating the connections between green entrepreneurial orientation, green innovation, and green marketing strategies in the context of sustainable business practices. The literature review reveals that environmental sustainability significantly shapes contemporary business strategies. The emergence of CSV as a business strategy underscores the integration of corporate success with positive contributions to society and the environment. The synthesized results highlight the theoretical relationships between green entrepreneurial orientation, green innovation, and green marketing strategies with sustainable business performance. Building upon the results, the discussion interprets the implications of the identified relationships and their significance in the realm of sustainable business strategies. This article enriches the academic literature by providing a conceptual framework for understanding sustainable business strategies. Additionally, the findings offer practical support for businesses in formulating sustainable strategies, guidance on integrating green innovation, and serve as a valuable reference for policymakers. Keywords: creating shared value, green entrepreneurial orientation, green innovation, green marketing strategies, sustainable business performance